High uptake of 2,4,6-trinitrotoluene by vetiver grass – potential for phytoremediation? - Shakya, Kabindra Man; Datta, Rupali K.; Sarkar, Dibyendu; Pachanoor, Devanand; Makris, Konstantinos C. (My University, 2007)
2,4,6-Trinitrotoluene (TNT) is a potent mutagen, and a Group C human carcinogen that has been widely used to produce munitions and explosives. Vast areas that have been previously used as ranges, munition burning, and open detonation sites are heavily contaminated with TNT. Conventional remediation activities in such sites are expensive and damaging to the ecosystem. Phytoremediation offers a cost-effective, environment-friendly solution, utilizing plants to extract TNT from contaminated soil. We investigated the potential use of vetiver grass (Vetiveria zizanioides) to effectively remove TNT from contaminated solutions. Vetiver grass plants were grown in hydroponic systems containing 40 mg TNT L−1 for 8 d. Aqueous concentrations of TNT reached the method detection limit (∼1 μg L−1) within the 8-d period, demonstrating high affinity of vetiver for TNT, without any visible toxic effects. Results from this preliminary hydroponic study are encouraging, but in need of verification using TNT-contaminated soils.
Keywords: Vetiver grass; TNT; Phytoremediation; Hydroponic study